2001
DOI: 10.1021/jo015826d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of (R)- and (S)-N-Protected 3-Hydroxypyrrolidines by Hydroxylation with Sphingomonas sp. HXN-200, a Highly Active, Regio- and Stereoselective, and Easy to Handle Biocatalyst

Abstract: Hydroxylation of N-benzylpyrrolidine 8 with resting cells of Sphingomonas sp. HXN-200 gave N-benzyl-3-hydroxypyrrolidine 15 in 53% ee (S) with an activity of 5.8 U/g CDW. By changing the "docking/protecting group" in pyrrolidines, hydroxylation activity and enantioselectivity were further improved and the enantiocomplementary formation of 3-hydroxypyrrolidines was achieved: hydroxylation of N-benzoyl-, N-benzyloxycarbonyl-, N-phenoxycarbonyl-, and N-tert-butoxycarbonyl-pyrrolidines 9-12 gave the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…It should be noted that WT P450pyr was known to be completely regioselective at the inactivated 3 position (53 % ee ( S )), with no reaction occurring at the activated N‐benzylic position where the CH bond strength is expected to be considerably lower 26. 27 Specific positioning of a substrate in the binding pocket of P450 enzymes, whatever the underlying factors may be, determines regioselectivity. In the case of P450pyr acting as a catalyst in the 3‐selective hydroxylation of N ‐benzyl pyrrolidine, reversal of enantioselectivity of up to 83 % ee had previously been achieved by utilizing iterative saturation mutagenesis (ISM) 4c.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that WT P450pyr was known to be completely regioselective at the inactivated 3 position (53 % ee ( S )), with no reaction occurring at the activated N‐benzylic position where the CH bond strength is expected to be considerably lower 26. 27 Specific positioning of a substrate in the binding pocket of P450 enzymes, whatever the underlying factors may be, determines regioselectivity. In the case of P450pyr acting as a catalyst in the 3‐selective hydroxylation of N ‐benzyl pyrrolidine, reversal of enantioselectivity of up to 83 % ee had previously been achieved by utilizing iterative saturation mutagenesis (ISM) 4c.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated that Sphingomonas sp. HXN-200 bacteria contain hydrocarbon-degrading enzymes [17,18]. The results of these studies suggest that Sphingomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…To further demonstrate the generality of this method, enantioselective biohydroxylation of N ‐benzylpyrrolidine ( 7 ) at the 3‐position was selected as another example. This represents an enantioselective hydroxylation of a nonactivated carbon atom, a symmetric substrate with equal CH bonds at the 3‐ and 4‐positions, and a useful transformation to prepare the corresponding product ( S )‐ 8 or ( R )‐ 8 , which is a key synthetic intermediate for several pharmaceuticals 20…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning, Sphingomonas sp. HXN‐200, a known biocatalyst for the hydroxylation of non‐activated carbon atoms,20 was selected as the catalyst. Biohydroxylation was performed with 5 m M ( R )‐ 9 or ( S )‐ 9 in a cell suspension (5.5 g cdw L −1 ) in 50 m M potassium phosphate buffer (5 mL, pH 7.5) containing glucose 2 % (w/v) at 30 °C for 1 h. Samples were taken directly from the aqueous biotransformation mixtures and analyzed by LC/MS; typical chromatograms are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%